1988
DOI: 10.1002/aoc.590020409
|View full text |Cite
|
Sign up to set email alerts
|

Comparative chronic toxicity, including tumorigenicity, of gallium arsenide and arsenic trioxide intratracheally instilled into hamsters

Abstract: Chronic toxicity, including tumorigenicity, of gallium arsenide (GaAs) and arsenic trioxide (As203) were studied using Syrian golden hamsters given intermittent intratracheal instillations. GaAs particles (0.25 mg x 15 timedanimal) were likely to produce relatively severe lung damage and the survival of the animals was shortened significantly compared with a control group. The tumor incidence of each group examined was GaAs (3.3%), As,O, (3.3%) respectively, at a dose of 3.75 mg total metal given during 15 wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…p > 0.05). A study using IT instillation of gallium arsenide in hamsters has critical design flaws, including short duration, small group sizes, etc., and shows no indication of tumors (Ohyama et al, 1988). Therefore, the conclusions that can be drawn about the IT carcinogenicity of arsenic from these particular studies must be considered limited.…”
Section: Intratracheal Instillationsmentioning
confidence: 99%
“…p > 0.05). A study using IT instillation of gallium arsenide in hamsters has critical design flaws, including short duration, small group sizes, etc., and shows no indication of tumors (Ohyama et al, 1988). Therefore, the conclusions that can be drawn about the IT carcinogenicity of arsenic from these particular studies must be considered limited.…”
Section: Intratracheal Instillationsmentioning
confidence: 99%
“…Pulmonary tumours developed in animals treated with calcium arsenate, but not in those treated with arsenic trisulphide. Recently, Ohyama et al (1988) reported that neither arsenic trioxide nor gallium arsenide caused tumours when administered by intratracheal instillation to Syrian golden hamsters once a week for 15 weeks. Osswald and Goerttler (1971) reported a study in which pregnant Swiss mice received subcutaneous injections of 0.005% sodium arsenate (0.5 mg As kg -1) for 20 days.…”
Section: Tntratracheal Instillationmentioning
confidence: 99%
“…Intratracheal instillation of GaAs particles (particle characteristics not specified) into Syrian golden hamsters (1.5 mg/kg bw) once per week for 15 weeks caused severe and long-lasting pulmonary toxicity characterized by alveolar cell hyperplasia, congestion with hemorrhage, and pneumonia (Ohyama et al, 1988). In this study severe lung toxicity was observed at clearly lower dose levels as compared to those applied by Omura et al (1996b).…”
Section: Study With Intratracheal Administration To Hamstersmentioning
confidence: 61%